2011
DOI: 10.1007/s11912-011-0186-8
|View full text |Cite
|
Sign up to set email alerts
|

Newly Emerging Therapies Targeting Viral-Related Lymphomas

Abstract: Gamma-(γ)-herpes virus lymphomas comprise a heterogenous group of B-cell and T-cell neoplasms most commonly associated with Epstein Barr virus (EBV) and rarely human herpes virus-8 (HHV-8) infection. Adult T-cell leukemia/lymphoma (ATLL) is a unique disease entity caused by the human T-cell lymphotrophic virus, type 1 (HTLV-I), the only retrovirus known to cause cancer in humans. Viral lymphomas behave aggressively and disproportionally affect immunocompromised individuals and those living in underdeveloped re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…In addition, novel, non-self tumor-specific antigens are created by gene fusions such as occurs in chromosome translocations, for example BCR-ABL1 [6], or are expressed in tumors of viral origin [7,8]. Finally, several antigens have been identified that are products of aberrant translation or splicing in tumors such that novel epitopes are generated from normally non-translated regions of mRNA [9,10], created by ribosomal frameshifting [11], or expressed from introns that fail to be spliced from the mature transcript [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, novel, non-self tumor-specific antigens are created by gene fusions such as occurs in chromosome translocations, for example BCR-ABL1 [6], or are expressed in tumors of viral origin [7,8]. Finally, several antigens have been identified that are products of aberrant translation or splicing in tumors such that novel epitopes are generated from normally non-translated regions of mRNA [9,10], created by ribosomal frameshifting [11], or expressed from introns that fail to be spliced from the mature transcript [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging targeted therapy makes it all the more important to identify infected cancers and to characterize biochemical defects such as ERBB2 overexpression that increases likelihood of response to trastuzumab in metastatic gastric cancer patients [16-18]. EBV-infected compared to uninfected gastric cancer has a favorable prognosis [19], and clinical trials are beginning to explore virus-targeted therapy such as 1) infused EBV-specific cytotoxic T cells or NK cells [20-23], 2) reversing the EBV-related methylator phenotype [24], 3) triggering lytic viral replication that could then incite the body’s innate and adaptive immune responses to kill infected tumor cells [25-33], and 4) lytic induction therapy co-administered with antiviral nucleoside analog such as gancyclovir that is phosphorylated and thus activated by viral kinases promoting cytotoxicity [34-41].…”
Section: Introductionmentioning
confidence: 99%
“…Vorinostat induced 30% response rates (Olsen et al, 2007), while Romidepsin induced 34% response rates (Whittaker et al, 2010). Combining valproic acid, a first generation HDACI, with AZT/IFN as a maintenance therapy was tested in 13 ATL patients (Ramos and Lossos, 2011).…”
Section: Histone Deacytelase Inhibitorsmentioning
confidence: 99%